Probing the general axion-nucleon interaction in water Cherenkov experiments - Maël Cavan-Piton; Diego Guadagnoli; Axel Iohner; Pablo Fernández-Menéndez; Ludovico Vittorio (Journal of High Energy Physics)
Abstract We consider an axion flux on Earth consistent with detectability at a Cherenkov-light facility such as the Hyper-Kamiokande neutrino experiment, implying emission from a sufficiently nearby Supernova candidate. Using Chiral Perturbation Theory augmented with an axion, we calculate the energy spectrum of a + N → N + γ as well as a + N → N + π 0, where N denotes a nucleon in the water tank planned for Hyper-Kamiokande. Our calculations assume the most general axion-quark interactions, with couplings constrained either solely by experimental data, or by specific theory scenarios. We find that even for the QCD axion — whose interaction strength with matter is at its weakest as compared with axion-like particles — the expected Cherenkov -light spectrum from neutrino-nucleon interactions is modified in a potentially detectable way. Furthermore, detectability appears significantly more promising for the N + π 0 final state, as its spectrum peaks an order of magnitude higher and at energies twice as large compared to the N + γ counterpart. Given the rarity of SN events where both the neutrino and the hypothetical axion burst are detectable, we emphasize the importance of identifying additional mechanisms that could enhance such signals.